Do Markets Favor Women?s Human Capital More than Planners? - Daniel Münich; Jan Svejnar; Katherine Terrell (Institute for the Study of Labor (IZA), 2004)
Using micro data on women in the Czech Republic, we compare returns to various measures of human capital at the end of communism (1989), in mid-transition (1996) and in late/posttransition (2002). We show: dramatic increases in returns to education from 1989 to 1996 but no change from 1996 to 2002; no differences in returns to education by state vs. privatelyowned firms; ?sheepskin? effects in both regimes, which rise over time and are similar across firm ownership; no difference in returns to education obtained during communism vs. transition; no change in wage-experience profiles over time; and similar increases in returns to education for women and men. In sum, markets pay women and men equally more for their human capital than the planners did; all the adjustment occurred in early transition and was driven by market forces rather than private ownership.
Keywords: P31; P20; J31; J24; 330; human capital; wages; transition; sheepskin effects; Czech Republic; Humankapital; Bildungsertrag; Geschlecht; Lohnniveau; Tschechische Republik